Extrinsic and Intrinsic Signalling Pathways That Regulate Stem Cell Developmental Potential - Price, Feodor duPasquier (Université d'Ottawa / University of Ottawa, 2012)
Instructive signals, whether external or internal, play critical roles in regulating the developmental potency or ability to self-renew of stem cells. External signals may range from secreted growth factors to extracellular matrix proteins found in the stem cell niche. Internal signals include activated signalling cascades and the eventual transcriptional mechanisms they initiate. In either fashion, stem cells are regulated in a complex temporal and context specific manner in order to maintain or maximise their unique characteristics. Previous experiments suggest that Wnt3a plays a role in maintaining the pluripotent state of mouse embryonic stem (mES) cells. However, in the absence of leukemia inhibitory factor (LIF), Wnt signalling is unable to maintain ES cells in the undifferentiated state. This implies that maintaining the pluripotent state of mES cells is not the primary function of canonical Wnt signalling. To further characterize the role of Wnt3a in pluripotency and lineage specification undifferentiated and differentiated mES cells were induced with Wnt3a. Wnt3a induced the formation of a metastable primitive endoderm state and upon subsequent differentiation, the induction of large quantities of visceral endoderm. Furthermore, we determined that the ability of Wnt3a to induce a metastable primitive endoderm state was mediated by the T-box transcription factor Tbx3. Our data demonstrates a novel role for Wnt3a in promoting the interconversion of undifferentiated mES cells into a pluripotent primitive endoderm state. Aging of skeletal muscle tissue is accompanied by fibrosis, atrophy and remodeling all of which negatively affect muscle performance. Whether this reduction in skeletal muscle competency is directly attributed to a resident adult stem cell population called satellite cells remains largely unknown. Here, we undertook an investigation into how age affects the transcriptional profile of satellite cells and their repopulating ability following transplantation. We determined that as satellite cells age, both their regenerative capacity and ability to colonize the satellite cell niche is reduced. Additionally, we identified satellite cell specific transcriptional profiles that differed with respect to age. Therefore, we conclude that intrinsic factors are an important determinant of satellite cell regenerative capacity during the aging process.
Keywords: Embryonic Stem Cells; Primitive Endoderm; Age; Satellite Cell; Wnt; Metastability